An Empirical Method of Estimating Soil Thermal Inertia - Jing Tian (Advances in Meteorology, 2015)
A method of estimating soil thermal inertia (STI), which uses midday soil heat flux (Gm) and diurnal surface temperature amplitude as the inputs, is presented in the paper. Gm is achieved from an empirical relationship between net radiation (Rn) and soil heat flux (G). To validate the STI method, a method proposed by Verhoef, which requires STI and a Fourier series analysis on surface temperature, is used to estimate diurnal G. By comparing diurnal G estimates and diurnal G measurements, the STI method is evaluated indirectly. The results show that the diurnal curve of G estimates can coincide with that of G measurements for bare soil, with the correlation coefficient (R2) of 0.64, bias of 10.1 W·m−2, and root mean squared errors (RMSE) of 40.9 W·m−2. For the vegetated surface, R2 is 0.56, bias is −11.9 W·m−2, and RMSE is 49.2 W·m−2. The large uncertainty in the estimation of Gm resulting from the wider variation of the empirical relationship between Rn and G and the difference between mixed surface temperature and soil surface temperature may be the two primary factors for the larger deviation of the diurnal shape and the magnitude between G estimates and G measurements for the vegetated surface.